Analisis Dinamika Psikologis Korban Kekerasan Dalam Pacaran Dari Perspektif Teori Konflik Galtung - Husnul Khotimah; Mernon Yerlinda C. Mage; Noorce Ch. Berek (Wacana Psikokultural, 2023)
This study intends to describe the psychological dynamics by revealing more deeply about the feelings, thoughts, and behaviors experienced by female students who are victims of dating violence. This study uses a qualitative approach in a descriptive form and uses a case study technique. This study uses observation, interview and documentation techniques to understand the attitudes, views, feelings, and behavior of victims in depth. Researchers try to explore the response that appears in victims of dating violence. There were 5 participants in this study, who were obtained through the snowball sampling technique. Based on the research conducted, it can be concluded that each victim who experiences dating violence has different psychological dynamics, namely actions or real events that occur to participants in the study, as well as an overview of psychological dynamics from the perspective of Galtung's ABC conflict theory which includes Contradiction, Attitude and Behavior